Effects of a selective cyclooxygenase-2 inhibitor on endometrial epithelial cells from patients with endometriosis - Olivares, Carla Noemi (2008)
Celecoxib, a selective cyclooxygenase (COX)-2 inhibitor, also has anti-proliferative properties and pro-apoptotic effects on different in vivo and in vitro models, two actions that may be efficacious in therapy for endometriosis. We evaluated the effects of celecoxib on apoptosis and proliferation, and vascular endothelial growth factor (VEGF) production and COX-2 expression and activity in endometrial epithelial cells (EECs).